New Scenarios, Actors, and Educational Practices Where Coexistence, Diversity, and Culture Are Built - Rosero-Prada, Ana Lucia (2022)
Introduction. Colombia has a variety of territories, people, cultures, political, and religious affiliations; however, it has been affected by a history of violence, inequality, corruption, among other evils, associated with the lack of tolerance for differences and the lack of protection for communities and minorities. Objective. The study was proposed to unveil the knowledge produced by organizations, their cultural modes of knowledge construction, intercultural learning, practices, and knowledge. As a counter-hegemonic bet, it was proposed to make them visible by considering their territories, life stories, and experiences. Method. The study was conducted from participatory action research, with 38 co-researchers from 13 organizations through pedagogical/research meetings, visits to territories, reflection circles, and interviews. Results. The study identified lines of flight analyzed from the perspective of the decolonization of aesthetic, epistemic manifestations, and the configuration of pedagogy in a territory as a vehicle of relations, the care of oneself and others in common spaces from dialogues, and plurilogical and multicultural practices. Conclusions. It is possible to demonstrate the recognition of an epistemic diversity and another pedagogy, that is, a call for other logics/rupture of the unitary idea of the world. Within the educational process of organizations, it is also possible to find paths to educate differentials, where educational concepts and methods are removed from the past and presented as everyday events that are interrogated in deliberative spaces.